Pengaruh Kinerja Lingkungan, Biaya Lingkungan, dan Operating Efficiency Terhadap Kinerja Perusahaan: Studi Kasus Perusahaan Sektor Pertambangan yang Terdaftar di BEI 2021-2023 - Moh Adrifat Suila; Hartati Tuli; Nurharyati Panigoro (Economic Reviews Journal, 2025)
This research aims to determine the influence of environmental performance, environmental costs, and operating efficiency on company performance. The type of method used in this research is a quantitative method with data collection techniques using secondary data and library data. The number of samples in this research is 45 samples in 2021-2023. The tool used in this research uses multiple linear regression analysis. The results of this research show that the influence of environmental performance, environmental costs and operating efficiency variables on company performance which can be explained by this equation is 58.1%. Meanwhile, the remaining 41.9% is influenced by other variables not included in the regression model. Good environmental performance contributes positively to company performance. Companies that implement environmentally friendly practices and focus on sustainability not only improve their reputation but can also reduce operational risks and take advantage of new market opportunities. Environmental costs incurred by companies to meet environmental standards or implement environmentally friendly technologies tend to have positive long-term results on company performance. High operating efficiency has a positive impact on company performance. By optimizing processes and reducing waste, companies can increase productivity and reduce costs.